A reanalysis of the Hitachi cohort study evaluating the effectiveness of low-dose CT screening for lung cancer - Keisuke Fukui; Takeshi Nawa; Tomio Nakayama; Motoyasu Sagawa (Japanese Journal of Clinical Oncology, 2026)
Abstract The effectiveness of low-dose thoracic computed tomography (CT) screening for lung cancer for non-smokers or light smokers has been unclear. The results of the Hitachi cohort study performed by the conventional multivariable analysis suggested the reduction of lung cancer mortality by thoracic CT screening, but also revealed the lower all-cause mortality in the CT group, which indicated the existence of self-selection bias. Because the background of the subjects in the CT screening group and that in the X-ray screening group were very different, it is critical to adjust appropriately the confounding factors. In this brief report, we describe a re-evaluation of the results of the Hitachi Cohort Study performed by using more flexible methods, propensity score matching and inverse probability weighting.